Neutralization of Pseudomonas aeruginosa enzymatic activity by antibodies elicited with proteins of Larrea divaricata Cav. - Sasso, Corina Verónica (2012)
Larrea divaricata Cav. (Jarilla) is a bush widely used in folk therapy for the treatment of several pathologies. Partially purified proteins of crude extract (JPCE) cross-react with proteins of Gram-negative bacteria, including Pseudomonas aeruginosa, which is an opportunistic pathogen that causes several intrahospitalary infections. This bacterium produces many proteins with enzymatic activity, including hemolysins and proteases that play a major role in acute infection caused by this bacterium. The aim of our work was to investigate if antibodies against with L. divaricata neutralize the hemolytic and proteolytic activity of P. aeruginosa. The hemolytic activity of soluble cellular proteins was inhibited 100% and extracellular proteins (EP) showed an inhibition between 44 and 95% when both bacterial fractions were treated with anti-JPCE serum. Also, in EP the neutralization was directed towards the active site of the hemolysin. When protease activity of extracellular products was tested, bands of 217, 155, 121, 47 and 27kDa were observed in native zymograms. Neutralization between 55 and 70% of the bands of 217, 155 and 121kDa was observed when EP were treated with anti-JPCE serum. In conclusion, our data clearly demonstrate that antibodies elicited with L. divaricata' proteins are able to neutralize the hemolytic and proteolytic activity of P. aeruginosa cellular and extracellular proteins. Our study constitutes the first report that associates the immunogenicity of plant proteins and bacterial proteins with enzymatic activity. These findings could be relevant in the development of alternatives therapies for patients suffering intrahospitalary opportunistic infections with P. aeruginosa. © 2012 Informa Healthcare USA, Inc.